Review of the 1991 Madrid Protocol - Sullivan, Nita (University of Canterbury, 2017)
In an environment as fragile and influential as Antarctica, protection and preservation guidelines form an important part of human interaction and governance. As the Antarctic Treaty system developed over the 20th Century, environmental issues moved to the forefront of the international discussion. Signed in 1991 and ratified in 1998, the Protocol on Environmental Protection to the Antarctic Treaty was viewed as a ground-breaking legal document, with the capability of enhancing the protection of the Antarctic environment through a comprehensive ecosystem approach. Today, the Protocol is met with significant criticism around issues of implementation, human impacts, and its ability to meet new and distinct environmental challenges. In this review, the successes and failures of the Madrid Protocol will be examined, with the literature showing widespread discontent with the Protocol's environmental capabilities. These perspectives reflect an increasing urgency around the need for changes to be made to the Treaty system, in order to maintain the Antarctic environment for future scientific research, tourism, and other human related activities.